Pegging the Renminbi to a basket: Facts, prospects and consequences - Heikki Oksanen (Center for Economic Studies and ifo Institute (CESifo), 2010)
On 19 June 2010 the Chinese authorities announced that the renminbi (RMB) was henceforth to be pegged to a currency basket. Yet, it has quite closely followed the USD, though having appreciated by 2.7 % by the time of writing. At the G20 Seoul Summit on 11-12 November 2010, China committed to further reform the RMB exchange rate regime. We discuss here what a genuine basket peg could mean for China, with the view that the weight for the EUR should obviously be significantly increased, the SDR being a strong option for practical implementation. This would also have a positive impact on the EU. China's currency reform has possible implications for its USD-dominated assets. Their reduction could trigger a further depreciation of the USD. The potentially costly consequences call for new rules for the world financial architecture. China's expansion will inevitably lead to a diminishing international role for the USD.
Keywords: F30; F31; F33; F42; 330; China; renminbi; yuan; basket peg; foreign exchange rates; Renminbi; Währungskorb; Fester Wechselkurs; Wechselkurssystem; Währungsreform; China